2021
DOI: 10.1186/s12939-020-01356-4
|View full text |Cite|
|
Sign up to set email alerts
|

A qualitative study of barriers to employment experienced by people living with HIV in Toronto and Ottawa

Abstract: Background Effective treatment has extended the life expectancy and reduced disability in people living with HIV (PLWH). However, previous research has found 45–65% of working-age PLWH were unemployed compared to 5–10% in the general public of North America and Europe. We examined the barriers to gaining employment among PLWH. Methods Thirty-five in-depth interviews were conducted in person or over the phone with PLWH living in Toronto or Ottawa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…HIV‐related stigma and its relationships with resource insecurity require multi‐faceted approaches. Structural interventions can address PLHIV's employment barriers, including workplace stigma, universal ART coverage and unpredictable periodic disability [54, 55]. Addressing housing insecurity could be integral to reducing HIV‐related stigma [23].…”
Section: Discussionmentioning
confidence: 99%
“…HIV‐related stigma and its relationships with resource insecurity require multi‐faceted approaches. Structural interventions can address PLHIV's employment barriers, including workplace stigma, universal ART coverage and unpredictable periodic disability [54, 55]. Addressing housing insecurity could be integral to reducing HIV‐related stigma [23].…”
Section: Discussionmentioning
confidence: 99%
“…HIV remains highly stigmatised, and discrimination and other manifestations of stigma contribute to the social isolation and mental health problems that are commonly reported by PLHIV [ 19 22 ]. Periodic disability as well as stigma and discrimination have limited the employment opportunities of many PLHIV, with consequences for their material well-being and long-term financial security [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, half of our patients were employed, which was also reported by several other studies [ 16 , 17 ]. Employment in PLHIV can have positive outcomes on their social interactions, economic status, self-esteem, and mental health, as well as their country’s economy [ 18 , 19 ]. In Saudi Arabia, the government issued a law to ensure that Saudis infected with HIV have the right to sustain their work status and education.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it has been found that PLHIV experiences unemployment rates three times higher than the average national unemployment rates [ 20 ]. Possible reasons for unemployment of PLHIV may include stigma, discrimination, restrictive policies and practices, and HIV-related illnesses [ 19 ]. However, this figure is changing due to the advancement in HIV treatment, particularly with the introduction of ARTs which have shown to have a positive impact on both job retention and the time needed to return to work in PLHIV [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%